2020
DOI: 10.18632/aging.103431
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the expression of microRNA-126-5p in the temporal muscle can promote angiogenesis in the chronically ischemic brains of rats subjected to two-vessel occlusion plus encephalo-myo-synangiosis

Abstract: Background: miR-126-5p plays an important role in promoting endothelial cell (EC) proliferation. We thus explored whether miR-126-5p can promote EC proliferation and angiogenesis in chronically ischemic brains (CIBs). Results: Improved revascularization in moyamoya patients was correlated with upregulated miR-126-5p expression in the TM and DM. In vitro experiments showed that miR-126-5p promoted EC proliferation through the PI3K/Akt pathway. CIBs from the agomir group exhibited significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…36 Two-vessel occlusion adaptations, such as staged ligation, have been described to counter these issues. 15,37 While a grossly similar reduction in CBF (average of 24.18% of baseline) has been observed, this modification affords a more progressive decline that may mitigate acute deficit. Unilateral occlusion of the CCA has also been described.…”
Section: Carotid Artery Occlusion or Stenosismentioning
confidence: 70%
See 1 more Smart Citation
“…36 Two-vessel occlusion adaptations, such as staged ligation, have been described to counter these issues. 15,37 While a grossly similar reduction in CBF (average of 24.18% of baseline) has been observed, this modification affords a more progressive decline that may mitigate acute deficit. Unilateral occlusion of the CCA has also been described.…”
Section: Carotid Artery Occlusion or Stenosismentioning
confidence: 70%
“…Surgical models utilize mechanical occlusion or narrowing of extracranial and/ or intracranial vasculature to replicate stenosis and accompanying cerebral ischemia. 15,16 Immunological models attempt to induce a "vasculitic" syndrome to reproduce the morphological changes observed in the intracranial vasculature of patients with MMD. 17,18 Finally, with the identification of the RNF213 susceptibility gene, various knockout, knock-in, or knockdown genetic models have been generated to study its impact on vasculogenesis, angiogenesis, and remodeling.…”
mentioning
confidence: 99%
“…As previously described ( 25 ), 30 μg protein samples were separated by 10% SDS-PAGE gel, and then transferred to polyvinylidene fluoride (PVDF, pore size, 0.45 um) membranes (Millipore Billerica, USA). The membranes were blocked with 5% non-fat dry milk for 1 h, followed by incubation overnight at 4°C with the following primary antibodies: rabbit anti-SH3RF2 (1:1,000), rabbit anti-HMGB1 (1:1,000), mice anti-EGFP (1:1,000, mice anti-GAPDH (1:1,000), and mice anti-β-actin (1:1,000).…”
Section: Methodsmentioning
confidence: 99%
“…Fang et al demonstrated that miR‐29b suppresses tumor angiogenesis, invasion, and metastasis by regulating matrix metalloproteinase 2 expression 20 . Chen et al demonstrated that increasing miR‐126‐5p expression in the temporal muscle can promote endothelial cell proliferation and angiogenesis in chronically ischemic brains of two‐vessel occlusion plus EMS rats through the PI3K/Akt pathway 21 …”
Section: Introductionmentioning
confidence: 99%
“… 20 Chen et al demonstrated that increasing miR‐126‐5p expression in the temporal muscle can promote endothelial cell proliferation and angiogenesis in chronically ischemic brains of two‐vessel occlusion plus EMS rats through the PI3K/Akt pathway. 21 …”
Section: Introductionmentioning
confidence: 99%